2020
DOI: 10.1016/j.devcel.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A Dedicated Evolutionarily Conserved Molecular Network Licenses Differentiated Cells to Return to the Cell Cycle

Abstract: Highlights d Dedicated genes govern paligenosis, a conserved cellular regeneration program d DDIT4 first blocks mTORC1, inducing massive autophagy to downscale the cell d p53 activation continues mTORC1 suppression to maintain cell quiescence d IFRD1 suppresses p53 to reinduce mTORC1 and license progression into the cell cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 72 publications
9
59
0
Order By: Relevance
“…Here, we observe striking transcriptional overlap between metaplastic cells in the pancreas and those of the stomach. Our results are in line with recent studies indicating that mature cells like gastric chief cells and pancreatic acinar cells have a shared injury-induced plasticity program, paligenosis, that governs their conversion from the differentiated to regenerative states 3, 25, 57 . Cycles of paligenosis that fuel pyloric metaplasia may allow cells to accumulate mutations and increase the risk for progression to cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we observe striking transcriptional overlap between metaplastic cells in the pancreas and those of the stomach. Our results are in line with recent studies indicating that mature cells like gastric chief cells and pancreatic acinar cells have a shared injury-induced plasticity program, paligenosis, that governs their conversion from the differentiated to regenerative states 3, 25, 57 . Cycles of paligenosis that fuel pyloric metaplasia may allow cells to accumulate mutations and increase the risk for progression to cancer.…”
Section: Discussionsupporting
confidence: 92%
“…ATF3 was previously characterized in the early stages of cerulein‐induced pancreatitis in mice (Fazio et al , 2017; Data ref: Fazio et al , 2017) and our in silico ‐predicted ATF3‐binding site matched a site from chromatin immunoprecipitation sequencing (ChIP‐Seq) analysis of genomic ATF3 binding early after cerulein injury from the published dataset (Fig EV3A–C). ATF3 was also an appealing target because it was previously described as one of the most highly upregulated genes in a mouse model of SPEM (Nozaki et al , 2008; Miao et al , 2020b). Thus, the data pointed to ATF3 as a key transcription factor early in paligenosis, potentially activating Rab7 to facilitate the massive autophagic changes in Stage 1.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that two genes meeting those criteria are Ddit4 (mentioned above) and Ifrd1 . DDIT4 is invoked early in paligenosis to quench mTORC1, which must be shut off for the massive autophagy and lysosomal activity of Stage 1, while IFRD1 is essential to restore mTORC1 activity for entry into S phase (Miao et al , 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs in response to various hormonal signals [ 172 ]. It is not clear whether the autophagy induced during reprogramming is under the control of TOR in plants, although cellular dedifferentiation followed by reactivation of cell proliferation in animals after wounding is controlled by the level of TOR activity, providing a precedent for a role for TOR also in plant cell reprogramming [ 173 ].…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%